Unintentional Injuries Requiring Medical Attention in Low-Income and Middle-Income Countries: Evidence from Nationally Representative surveys in 12 Countries - Leila Ghalichi; Albertino Damasceno; David Flood; Pascal Geldsetzer; Mongal Gurung; Maja Marcus; Kibachio Joseph Mwangi; Sebastian Vollmer; Michaela Theilmann; Justine Davies (Journal of Epidemiology and Global Health)
Abstract Background Despite a high burden of injuries in low-income and middle-income countries (LMICs), a lack of empirical evidence on mechanism, location, and distribution of unintentional injuries requiring medical attention (hereafter injuries) hinders informed health system policy development. Methods Using individual-level data from nationally representative surveys conducted in LMICs between 2014–2019, we describe the weighted annual prevalence of non-fatal injuries, their mechanisms, environments in which they occur, and characteristics of people injured, in individuals aged 15–64 years. Multivariable logistic regression models were estimated to evaluate associations of injuries with individual-level characteristics. Results We included data on 47,747 participants from 12 LMICs in four WHO regions. The weighted prevalence of non-fatal injuries in the past year was 6.8% (95% CI: 6.3%-7.2%); men suffered a greater prevalence of injuries than women (8.3% [95% CI 7.6%-9.0%] vs. 5.4% [95% CI 5.0%-5.9%], respectively). In the multivariable logistic regression, the odds of having any injury were lower among females and married people and higher among individuals with some primary education. Prevalence of non-road traffic collision injuries was almost threefold that of road traffic collision (RTC) injuries: 5.6% (5.2%-6.0%) vs. 1.7% (1.5%-2.0%). When considering non-RTC injuries, falls were the most common mechanism (47.0%, 95% CI 44.0%-50.1%), and homes were the most common location (38.1%, 95% CI 34.9%-41.4%), followed by road (17.9%, 95% CI 15.7%-20.4%), and workplace (17.4%, 95% CI 15.2%-19.8%). The largest proportion (23.2%, [95% CI 20.6%-25.9%]) of non-RTC injuries happened to women at home. Conclusion Non-RTC injuries, in particular falls, predominate in this population. This highlights a neglected side of injuries, many of which happen at home to women, whereas global attention tends to focus on RTCs. Data on all mechanisms of injuries and care-seeking behaviour after injuries are required for health system planning.